Retreat : a novel - Ritter, Krysten, 1981-; Jamieson, Lindsay (Harper, 2025)
"Liz Dawson weaves through a crowd with the ease of a tropical breeze, moving seamlessly through elite circles, sparking instant connections and making every new acquaintance feel like an intimate friend. She's clever, smooth, and confident--qualities that make her a brilliant serial con artist. Isabelle Beresford is strikingly beautiful, obscenely wealthy, and the new owner of Casa Esmerelda, a fabulous villa on the Mexican coast--attributes that make her the perfect mark. When she offers Liz a job handling the installation of a piece of art in her otherwise vacant home, Liz can't resist the allure of a beach retreat. She longs for a reset, a chance to finally shed the grip of her addiction to the conning game. But when Liz, with her lush dark hair and intense green eyes, is mistaken for Isabelle herself, Liz can't help effortlessly slipping into the socialite's identity. The transition is so easeful, it almost feels like fate. But just who is Isabelle Beresford really, and why does she seem to have abandoned this stunning life of hers? As Liz insinuates herself deeper into the dazzling--and deceptive--world of the Punta Mita resort community, she draws closer to the dangers surrounding the real Isabelle. Dangers that may have already ensnared Liz, too. This might not be the con of her life--but the con that ends it."--